Experimental Validation of a Numerical Model for the Prediction of the Vulcanization Degree of a Fiber Reinforced Elastomeric Isolator (frei) - Gaetano Pianese; Gabriele Milani; Federico Milani (Chemical Engineering Transactions, 2023)
Seismic isolation of a structure can be achieved by interposing a rubber device between the foundation and superstructure, which increases the period of the superstructure, resulting in a structure relatively transparent to seismic excitation. Alternating layers of rubber pads and steel laminas or Fiber Reinforced Polymer (FRP) dry textiles suitable treated, typically constitute an elastomeric seismic isolator. The rubber should be processed through several stages to be ready for structural application. One of the most critical is vulcanization. During this stage, rubber is heated with sulfur or peroxides, accelerators, and activators at around 130-160°C. This process triggers the formation of cross-links between long rubber molecules, creating the so called polymer network. The chains are prevented from sliding along each other thanks to cross-links, and the rubber becomes elastic. This study proposes a combined numerical and experimental approach to predict the vulcanization degree for a Fiber-Reinforced Elastomeric Isolator (FREI). According to the numerical results, two typologies of vulcanization have been considered: one suboptimal at 145°C for 5400 seconds and one optimal at 145°C for 7200 seconds. Results, in terms of Shore A hardness measurements, have shown a non-homogeneous distribution within the isolator suboptimal vulcanized. Instead, as expected, the hardness distribution is homogeneous for the optimal one.